Photoactive nanodevices for potential biological applications - Carboni, Valentina <1987> (Alma Mater Studiorum - Università di Bologna, 2015)
Biological systems are complex and highly organized architectures governed by noncovalent interactions, which are responsible for molecular recognition, self-assembly, self-organization, adaptation and evolution processes. These systems provided the inspiration for the development of supramolecular chemistry, that aimed at the design of artificial multicomponent molecular assemblies, namely supramolecular systems, properly designed to perform different operations: each constituting unit performs a single act, whereas the entire supramolecular system is able to execute a more complex function, resulting from the cooperation of the constituting components. Supramolecular chemistry deals with the development of molecular systems able to mimic naturally occurring events, for example complexation and self-assembly through the establishment of noncovalent interactions. Moreover, the application of external stimuli, such as light, allows to perform these operations in a time- and space-controlled manner. These systems can interact with biological systems and, thus, can be applied for bioimaging, therapeutic and drug delivery purposes. In this work the study of biocompatible supramolecular species able to interact with light is presented. The first part deals with the photophysical, photochemical and electrochemical characterization of water-soluble blue emitting triazoloquinolinium and triazolopyridinium salts. Moreover, their interaction with DNA has been explored, in the perspective of developing water-soluble systems for bioimaging applications. In the second part, the effect exerted by the presence of azobenzene-bearing supramolecular species in liposomes, inserted both in the phospholipid bilayer and in the in the aqueous core of vesicles has been studied, in order to develop systems able to deliver small molecules and ions in a photocontrolled manner. Moreover, the versatility of azobenzene and its broad range of applications have been highlighted, since conjugated oligoazobenzene derivatives proved not to be adequate to be inserted in the phospholipid bilayer of liposomes, but their electrochemical properties made them interesting candidates as electron acceptor materials for photovoltaic applications.